A modelling technique for calculating stress intensity factors for structures reinforced by bonded straps. Part I: Mechanisms and formulation - Boscolo, Marco; Zhang, Xiang (Elsevier, 2010)
This paper describes a 2D FE modelling technique for predicting fatigue crack growth life of integral structures reinforced by bonded straps. This kind of design offers a solution to the intrinsic lack of damage tolerance of integral structures. Due to the multiple and complex failure mechanisms of bonded structures, a comprehensive modelling technique is needed to evaluate important design parameters. In this Part I of a two-part paper, the actions and mechanisms involved in a bonded structure are discussed first, followed by presenting the modelling approaches to simulate each mechanism. Delamination or disbond of the strap from the substrate is modelled by computing the strain energy release rate on the disbond front and applying a fracture mechanics criterion. Thermal residual stresses arising from the adhesive curing process and their redistribution with the substrate crack growth are calculated and taken into account in the crack growth analysis. Secondary bending effect caused by the un-symmetric geometry of one-sided strap is also modelled. In the classic linear elastic fracture mechanics, a non-dimensional stress intensity factor, i.e. the geometry factor β, depends only on the sample’s geometry. This β factor cannot be found for this kind of bonded structures, since the magnitude of disbond is related to the applied stress and the disbond size modifies the geometry of the structure. Moreover, secondary bending effect is geometric nonlinear thus the stress intensity factor cannot be normalised by the applied stress. For these reasons an alternative technique has been developed, which requires calculating the stress intensity factors at both the maximum and minimum applied stresses for each crack length. This analysis technique is implemented in a computer program that interfaces with the NASTRAN commercial code to compute the fatigue crack growth life of strap reinforced structu
Keywords: Fatigue crack growth life; Bonded straps; Selective reinforcements; Thermal residual stress; Delamination; Disbond; Secondary bending; Bonded patch repair